Earplug use during sleep and its association with cardiovascular disease – Results from a large sample of the general population - Omar Hahad; Volker H. Schmitt; Rieke Baumkötter; Matthias Michal; Julian Chalabi; Alexander K. Schuster; Emilio Gianicolo; Karl J. Lackner; Katharina Geschke; Julia Weinmann-Menke; Stavros Konstantinides; Andreas Daiber; et al. (International Journal of Cardiology: Heart & Vasculature)
Introduction: Environmental factors contribute to cardiovascular disease (CVD) pathogenesis. Noise annoyance is linked to adverse cardiovascular outcomes, and earplug use may mitigate noise-related health effects. This study examines associations between earplug use, noise annoyance, and CVD in a general population sample. Methods: Cross-sectional data from 15,010 participants (35–74 years, 2007–2012) in the German Gutenberg Health Study were analyzed. Noise annoyance from various sources and earplug use during sleep were self-reported. Prevalent CVD (atrial fibrillation, coronary artery disease, myocardial infarction, stroke, chronic heart failure, peripheral artery disease, or venous thromboembolism) was determined through self-report or medical records. Logistic regression analyses with sequential adjustments evaluated associations. Results: Among 14,675 participants with earplug data, 713 (4.9%) reported use. Earplug users were more likely younger women with lower cardiovascular risk profiles but higher noise annoyance (90.3% vs. 78.8%). Logistic regression revealed consistent positive associations between earplug use and prevalent CVD across various noise sources, persisting after adjustments for covariates. For example, the odds ratio for earplug use and prevalent CVD, adjusted for neighborhood noise annoyance and other factors, was 1.91 (95% CI 1.39–2.59). No interaction between earplug use and noise annoyance was found. Conclusions: This study provides valuable insights into the relationships between earplug use, noise annoyance, and CVD. Findings highlight the need for targeted interventions addressing noise-related cardiovascular risks and emphasize the complex dynamics of these factors in cardiovascular health.